2020
DOI: 10.1002/esp.4795
|View full text |Cite
|
Sign up to set email alerts
|

A GIS method to identify flat surfaces and restore relict fluvial long‐profiles from terrace remnants gives new clues on how large basins respond to endorheic–exorheic transitions (Duero basin, Iberian Peninsula)

Abstract: Fluvial terraces are used as geomorphic indicators for deciphering long‐term landscape evolution. Knowing the distribution of fluvial terraces is essential for establishing former river profiles and their tectonic significance, for studying climate‐modulated processes of terrace development, or for defining fluvial network adjustments in response to sudden base‐level changes like those produced by fluvial captures. Multiple methods for automatic map production have been proposed based on the comparison of morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…However, the age-height transfer curve reported for the Duero river in their work was supported on the few numerical ages available for the Arlanzón tributary, close to the source area of sediments in the Iberian Chain (Figure 1). Finally, an older opening age range of ~3.7-1.8 Ma has been recently reported based on an extrapolation of incision rates derived from strath terraces hanging at +53-48 m (360->230 ka), +34-27 m (57 ka) and +17-13 m (39-12 ka) between Pocinho and Barca d'Alva (Cunha et al, 2019), downstream of the Arribes knickzone, in the upper end of the Duero Lower Reach (DLR; -Rodríguez et al, 2020). The swath profile of maximum elevation shows the topographic signature of the LPS erosional surface, presumably linked to the initial emptying of the basin after the endo-exorheic transition.…”
Section: Geologic and Geomorphologic Background Of The Study Areamentioning
confidence: 99%
See 3 more Smart Citations
“…However, the age-height transfer curve reported for the Duero river in their work was supported on the few numerical ages available for the Arlanzón tributary, close to the source area of sediments in the Iberian Chain (Figure 1). Finally, an older opening age range of ~3.7-1.8 Ma has been recently reported based on an extrapolation of incision rates derived from strath terraces hanging at +53-48 m (360->230 ka), +34-27 m (57 ka) and +17-13 m (39-12 ka) between Pocinho and Barca d'Alva (Cunha et al, 2019), downstream of the Arribes knickzone, in the upper end of the Duero Lower Reach (DLR; -Rodríguez et al, 2020). The swath profile of maximum elevation shows the topographic signature of the LPS erosional surface, presumably linked to the initial emptying of the basin after the endo-exorheic transition.…”
Section: Geologic and Geomorphologic Background Of The Study Areamentioning
confidence: 99%
“…Either a younger opening age for the Duero Basin compared to other Iberian basins (> 3 Ma according to Antón et al, 2019;~3.7-1.8 Ma according to Cunha et al, 2019;1.1-1.9 Ma according to Silva et al, 2017) and/or the resistant lithology that configures the Duero basin fringe (Struth et al, 2019) could explain the differences observed in fluvial entrenchment in response to sudden base-level lowering caused by an endo-exorheic transition. Here, we target a sequence of thirteen inset fluvial strath terraces formed in response to the Duero endo-exorheic transition, which are now hanging at heights up to +136-128 m above the modern floodplain (Rodríguez-Rodríguez et al, 2020; Figure 2).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is independent on whether the opening is dominated by basin overfilling or by fluvial capture (piracy). The spillway and the just extended drainage basin then tend to adjust to the new base level (Howard et al, 1994) resulting in an upstream propagation of an erosion wave (e.g., Loget and Van Den Driessche, 2009;Struth et al, 2019;Rodríguez-Rodríguez et al, 2020a, 2020b. This retrogressive incision wave erodes the elevated low relief formed during the endorheic conditions.…”
Section: Introduction To Drainage Opening and Transient Topographymentioning
confidence: 99%